An integrated framework for mapping barriers and strategies in green hydrogen deployment - Ayyildiz, Ertugrul; Kesici, Busra; Erdogan, Melike; Cari, Melike; Aydin, Nezir (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
Green hydrogen is a pivotal pathway for achieving decarbonization across power production, industry processes, and transportation sectors. However, few studies simultaneously map the causal structure of adoption barriers and prioritize actionable strategies under interval-valued fuzzy uncertainty. This study questions which barriers are the key drivers of the system and which strategies provide the best compromise to accelerate deployment. We apply Interval-Valued Intuitionistic Fuzzy Decision-Making Trial and Evaluation Laboratory (IVIF-DEMATEL) to quantify interrelationships and weights for nine interdependent adoption barriers, and Interval-Valued Intuitionistic Fuzzy VIseKriterijumska Optimizacija I Kompromisno Resenje (IVIF-VIKOR) to rank six competing strategy alternatives against a multi-criteria set derived from the barrier landscape. The causal analysis identifies High Production Cost, Regulatory Uncertainty, and Technology Readiness as the three strongest driving barriers, whereas Lack of Infrastructure attains the highest overall prominence despite acting as an effect factor. On the strategy side, the compromise solution set consists of Technology Maturation and System Integration as the first-ranked option, followed by Regulatory Clarity, Certification, and One-Stop Permitting, indicating that technological readiness and regulatory certainty are the most effective leverage points for accelerating deployment. The study delivers an integrated IVIF framework that links causal weighting to strategy choice and offers a prioritized roadmap for policy and investment.
Keywords: Green hydrogen; Intuitionistic fuzzy numbers; Multi-criteria decision-making; Energy systems; Sustainability; DECISION-MAKING; SITE SELECTION; FUZZY-AHP; ENERGY; ROADMAP; TOPSIS; Chemistry; Electrochemistry; Energy & Fuels